Provincial Centers for Adult Education: A Welcoming Territorial Service Network - Giovanni Di Pinto (Pensa MultiMedia, 2022)
This contribution aims to reflect on the opportunities for inclusion that the CPIAs can offer to adults. The peculiarity of adult learners and the networked organization of the aforementioned centers suggest that managers and teachers involved in Adult Education open up to the territory, after analyzing it, in order to enter into fruitful educational alliances. The reading of the context and the interpretation of the skills needs of adult users must lead to a revision of the PTOF to make it more functional to the requests of the stakeholders and to the institutional purposes of the CPIAs which, as a reference for the creation of territorial networks for lifelong learning, must promote the raising of educational levels.